Conceptual design of out-of-roundness test equipment for aircraft wheels - Mohamad Shafiee, Mohd Sulhi; Saadon, Syamimi (Zhongguo Hangkong Taikong Xuehui, 2024)
Abnormal flight events such as hard and overweight landings will have an impact on the aircraft wheels. In this case, the aircraft wheels can be outof-roundness and cause further issues including vibrations and increased tire wear, which can affect the safety of the passengers. There are several methods that have been applied to measure the out-of-roundness of the aircraft wheels and one of them is the dial indicator. For this study, two conceptual designs of the out-of-roundness test equipment for aircraft wheels are developed. The designs are modelled in Autodesk software, which is also used to conduct the FEA simulation analysis on the design models. Three different materials are considered in this study to build the equipment and they are steel, Delrin and Nylon 6/6. Based on the simulation results, Design 1 has been shown to have a significantly better performance than Design 2. For Design 1, with regards to the material, all of them can appropriately satisfy the design requirements and correspond to comparable performance. Nonetheless, Delrin or Nyon 6/6 is proposed for use due to their added advantages.